Assessment of Quality of Suburban Building Stock Case Study: Bairro da Bouça,Porto, Portugal - Monteiro, Ana (2010)
The "Bairro da Bouça" social housing is one of the most emblematic interventions of the SAAL programme, devoted to create social housing for poor people in Porto in the 70s of the twentieth century. Projected by Álvaro Siza Vieira, the neighbourhood is located near Boavista, nowadays a central area in the city. It was built in two main steps, the initial 56 housing, in 1975, and the last 72, which were finally completed in 2006, also with the rehabilitation of the initial 56. The "Bairro da Bouça" was initially designed in order to fulfil the basic needs of housing in times of poverty (1974/5) and to integrate the residential community with social and economic problems into the surrounding community. It had a particular characteristic: it was a SAAL (Serviço Ambulatório de Apoio Local - Local Support Ambulatory Service) intervention, popular origin group that arose to create an institutional and organized framework to facilitate the dialogue between residents and public power. One of their intentions was to make it possible for the residents to intervene at any phase of the process, from the selection of projects, typologies, supervision of works, to the allocation and management issue. For the conclusion of this project it was essential the support of the cooperative movement. "Bairro da Bouça" is a neighbourhood where two periods of construction coexist, corresponding to different implementation models (residents association and cooperative) and, as consequence, to different socioeconomic levels. This paper presents "Bairro da Bouça" as an example of the economical, social and urban planning problems and answers in two different temporal contexts.